Influence Of Excitation Angles Of Ground Motion With Forward Directivity Effect On The Response Of Regular And Symmetric Reinforced Concrete Buildings - Defallah, Haneen Mosbah Rateb (2009)

(untitled)
Existing procedure of seismic analysis was to apply ground motion components at the principal axes, which may not produce a maximum structural response. In order to ensure an acceptable level of reliability of analysis when performing a design, it is important to find the critical excitation angle that produces the maximum structural response. To investigate values of inter-story drift ratio, the current research applied nonlinear inelastic dynamic analysis to a six story RC building with four different fundamental periods, by adjusting the inertia value of the models without redesigning the building. Seven sets of ground motions were applied at various angles (ranging from 0° to 170°) to each building. These ground motions exhibiting the forward directivity effect and the acceleration records were scaled up and down to account for more or less severe ground motions from the same record. Incremental dynamic analysis (IDA) curves were formed to study the effects of different excitation angles on the structural responses and to specify the critical excitation angle.